Pandangan al-Qurâan tentang Makna JÃ¢hilÃ®yah Perspektif Semantik - Romziana, Luthviyah (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
This article will examine the meaning of the word in the Koran jÃ¢hilÃ®yah mentioned as many as 24 verses in 17 letters with various forms of the semantic approach. This approach is an option given the existence of this word has been around since pre-islamic Arab past, as evidenced by the presence of all jÃ¢hilÃ®yah lyric. In addition, the commentators also provide a diverse meaning to the word. Ibn JarÃ®r al-TabarÃ® that in fact as a classical commentators, stating that the meaning of the word refers jÃ¢hilÃ®yah person who has committed a disgraceful act or any person who commits sin intentionally. While Sayyid Qutb see it as the opposite of âilm and maârifah. In view of Quraish Shihab is jÃ¢hilÃ®yah is not only opposed to the word âilm but also in the sense of losing control of himself, so that actors do things that are not fair, either at the instigation of appetite, temporary interests, or parochialism. Many differences of opinion about the meaning of the word jÃ¢hilÃ®yah, interesting to study further with semantics as analysis approach",